A method for resource utilization of aldehyde-containing wastewater to prepare anti-sulfur reversion agent pre-dispersion master batch
Patent Information
- Application Number
- CN202611345055.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-27
AI Technical Summary
醛类物质毒性大,环境危害严重,传统处理方式包括委托第三方处理或自建“脱醛+生化”组合工艺,均存在处理成本高、流程复杂、资源浪费等问题
[0022]通过上述技术方案,通过将前述各实施例制得的母粒直接投入密炼机与天然橡胶/顺丁橡胶/炭黑N234体系混炼,其中抗硫化返原剂以纳米级分散相(DLS测得Z-avg = 86nm)均匀分布于橡胶网络,其酰胺基团在硫化初期与多硫键竞争结合活性硫,抑制C–S键断裂重排,从而延缓交联网络降解;该作用机制在动态疲劳测试中体现为:使用本发明母粒的轮胎胎面胶在50℃×107次屈挠后裂口长度仅为对照组(粉体直投)的58%。
Smart Images

Figure CN122978643A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of environmental waste treatment technology, and in particular to a method for the resource utilization of pre-dispersed masterbatch for preparing anti-sulfurization reversion agent from aldehyde-containing wastewater. Background Technology
[0002] Rubber tackifiers (mainly modified phenolic resins) are important additives in the production of rubber products, generating wastewater containing 8%–15% aldehydes during their production. Aldehydes are highly toxic and pose serious environmental hazards. Traditional treatment methods, including outsourcing to third parties or building in-house "de-aldehyde + biochemical" combined processes, suffer from high costs, complex procedures, and resource waste. Furthermore, existing treatment methods only achieve harmlessness, not waste resource recovery, failing to address the conflict between environmental protection and cost at its source. Therefore, there is an urgent need for a resource utilization method that can completely eliminate aldehyde pollution and transform it into high-value-added products. Summary of the Invention
[0003] This application provides a method for the resource utilization of pre-dispersed masterbatch for preparing anti-sulfurization reversion agent from aldehyde-containing wastewater, in order to solve the above-mentioned problems. The method includes: S1. Formaldehyde-containing wastewater generated during the production of tackifying resin and urea are fed together at a molar ratio of formaldehyde to urea of 1.5 to 2.5:1. A condensation reaction is carried out in the presence of a catalyst. The condensation reaction is carried out in two stages: the first stage is carried out at 80 to 85°C for 0.5 to 1 hour, and the second stage is carried out at 105 to 110°C for 3 to 5 hours. S2. The reaction product obtained in step S1 is filtered and dried to obtain urea-formaldehyde resin. S3. The urea-formaldehyde resin obtained in step S2, the pure powder of citramide-type anti-sulfurization reversion agent, zinc stearate and microcrystalline wax are premixed and then melt-extruded, granulated and graded to obtain the anti-sulfurization reversion agent pre-dispersion masterbatch. The components in step S3, by mass, include: 25-35 parts of urea-formaldehyde resin, 30-40 parts of pure powder of citrate-type anti-sulfurization reversion agent, 15-25 parts of zinc stearate, and 10-20 parts of microcrystalline wax.
[0004] Through the above technical solution, by limiting the molar ratio of formaldehyde to urea to 1.5–2.5:1, and employing a two-stage temperature-controlled condensation strategy of 80–85℃ / 0.5–1h and 105–110℃ / 3–5h, the hydroxymethylation reaction and the dehydration condensation reaction proceed in a stepwise and orderly manner: the first stage, with low temperature conditions, inhibits excessive cross-linking and ensures the formation of linear intermediates; the second stage, with high temperature, promotes the formation of methylene bridges and the increase in molecular weight, thereby achieving a glass transition temperature (GMT) while ensuring a formaldehyde conversion rate >99.9%. This is a reprocessable urea-formaldehyde resin with a temperature range of 65–75℃ and a number-average molecular weight (Mn) of 2800–3500. The resin is rich in –NHCO– and –CH2– structural units, which not only form a hydrogen bond network with the amide groups in the limonamide-type anti-sulfurization reversion agent molecule to enhance compatibility, but also improve melt flowability through flexible methylene segments. This allows for uniform coating and spatial isolation of the anti-sulfurization reversion agent within the carrier matrix during subsequent blending and granulation, solving the problems of easy agglomeration, uneven dispersion, and large metering errors in pure powders.
[0005] Optionally, the formaldehyde content in the aldehyde-containing wastewater is 8% to 15%.
[0006] By limiting the formaldehyde concentration in aldehyde-containing wastewater to the range of 8% to 15%, the above technical solution ensures that the amount of formaldehyde per unit volume of wastewater is sufficient to drive the condensation reaction to generate urea-formaldehyde resin with sufficient thermal stability and mechanical strength (when formaldehyde < 8%, the resin yield drops to < 65%, and Mn < 2200, leading to fiber breakage during melt extrusion; when > 15%, the viscosity of the reaction system increases sharply, local exothermic reactions intensify, side reactions increase, and free formaldehyde residue rises to over 0.15%). Furthermore, it adapts to actual emission fluctuations in industrial settings, allowing wastewater to be directly fed without dilution or concentration, reducing pretreatment energy consumption and equipment investment. This concentration range, combined with a molar ratio of 1.5 to 2.5:1, ensures that the urea dosage is within the economically optimal range (urea excess < 10%), preventing unreacted urea residue in the masterbatch from causing delayed sulfidation.
[0007] Optionally, the catalyst in step S1 is p-toluenesulfonic acid or ammonium sulfate.
[0008] Through the above technical solutions, two pathways—proton acid catalysis and in-situ acidification catalysis—are constructed by selectively introducing p-toluenesulfonic acid or ammonium sulfate, respectively: p-toluenesulfonic acid, as a strong organic acid, can directly provide H+. +Accelerating the carbonylation of formaldehyde increases the hydroxymethylation rate by 2.3 times (compared to the initial reaction rate constant k1); ammonium sulfate decomposes at 105–110 °C to produce NH3 and H2SO4. NH3 reacts with unreacted formaldehyde to form hexamethylenetetramine intermediate, while H2SO4 continuously provides an acidic environment to promote polycondensation. The two work synergistically to extend the effective catalytic window; neither catalyst introduces halogens or heavy metal ions, thus avoiding contamination of the electrical properties and aging behavior of rubber products.
[0009] Optionally, the amount of catalyst added is 0.1% to 1.0% of the urea mass.
[0010] By precisely controlling the catalyst dosage within the range of 0.1% to 1.0% of urea mass, a balance between catalytic activity and side reaction inhibition is achieved: when <0.1%, the condensation reaction is incomplete, with residual formaldehyde reaching 0.23%; when >1.0%, the system pH <2.5, leading to excessive cross-linking of urea-formaldehyde resin, with a gel content >8%, making pressure filtration impossible; within this preferred range, the catalyst is sufficient to complete 90% hydroxymethylation within 1 hour at 82℃ in the first stage and 99.92% formaldehyde conversion within 4 hours at 108℃ in the second stage, while avoiding ring-opening of the urea ring or re-release of formaldehyde induced by a strong acid environment; this parameter, in synergy with the catalyst type, ensures the regularity of the resin structure and its thermoplasticity.
[0011] Optionally, after the reaction in step S1 is completed, a sample is taken for testing, and the reaction is terminated when the residual formaldehyde content is less than 0.1%.
[0012] By using the above technical solution and setting residual formaldehyde <0.1% as the reaction endpoint criterion, the toxicity risk is cut off at the source. This threshold is less than 1 / 3 of the free formaldehyde limit (0.3%) in GB / T 30772–2014 "Urea-Formaldehyde Resin Adhesives". Moreover, gas chromatography-mass spectrometry (GC-MS) confirmed that the residue is mainly bound hydroxymethylurea, with no free HCHO monomer. This control strategy, together with two-stage temperature control and catalyst dosage, forms a closed-loop feedback mechanism to ensure that the formaldehyde removal rate of each batch of product is ≥99.91%.
[0013] Optionally, the drying temperature in step S2 is 85–95°C.
[0014] By limiting the drying temperature to 85–95°C, a balance is achieved between efficient moisture removal and resin thermal stability. This temperature is higher than the boiling point of water but lower than the initial thermal decomposition temperature of urea-formaldehyde resin (Td5% = 112°C). The moisture content of the filter cake can be reduced from 45% to ≤0.5% within 3–4 hours. At the same time, it avoids excessively high temperatures that could cause the methylene ether bonds to break or deaminated crosslinking, leading to a rise in resin Tg to >80°C and loss of thermoplasticity. The loose density of the resin powder obtained by drying at 85–95°C is 0.48–0.53 g / cm³, and the angle of repose is <35°, which meets the requirements for uniform premixing with powder additives in high-speed mixers.
[0015] Optionally, the melt extrusion temperature in step S3 is 120–130°C.
[0016] Through the above technical solution, by controlling the melt extrusion temperature at 120–130℃, the components are placed within a synergistic plasticizing window: at this temperature, the melt index of urea-formaldehyde resin reaches 9.2–11.8 g / 10min, the pure powder of citramide-type anti-sulfurization reversion agent begins to soften but does not decompose (DSC shows the initial decomposition temperature is 142℃), zinc stearate completely melts and exerts a lubricating effect (melting point 125℃), and microcrystalline wax uniformly coats the particle surface in a liquid state; the apparent viscosity of the four-component melt is 1800–2200 Pa·s (125℃, 10 s⁻¹). - ¹), with a shear thinning index n = 0.31~0.35, ensures the stability of screw conveying and the consistency of die extrusion.
[0017] Optionally, the grading in step S3 is vibration grading.
[0018] By employing the above technical solution, vibration grading replaces traditional cyclone separation or screen oscillation. Utilizing a three-dimensional vibration field with an amplitude of 0.8–1.2 mm and a frequency of 15–18 Hz, the wet-heat masterbatch achieves high-frequency jumping and tumbling on the screen, efficiently removing fine powder (<1.5 mm) and oversized particles (>3.5 mm), achieving a qualified particle size yield of >94.5%. The vibration grading process is free from airflow disturbance, avoiding screen blockage caused by electrostatic adsorption of the anti-sulfurization reversion agent. Furthermore, after grading, the microcrystalline wax on the masterbatch surface redistributes to form a dense hydrophobic film, reducing the moisture absorption rate from 3.2% to 0.7%.
[0019] Optionally, the components in step S3 are preferably, by mass, 30 parts of urea-formaldehyde resin, 35 parts of citrate-type anti-sulfurization reversion agent pure powder, 20 parts of zinc stearate, and 15 parts of microcrystalline wax.
[0020] Through the above technical solution, a triple synergistic mechanism is constructed using this optimized ratio: 30 parts of urea-formaldehyde resin provide sufficient carrier skeleton and interfacial binding sites; 35 parts of citramide-type anti-sulfurization reversion agent ensures high active component loading while avoiding excessive concentration leading to a sharp increase in melt viscosity; 20 parts of zinc stearate and 15 parts of microcrystalline wax form an "internal lubrication + external lubrication" composite system—zinc stearate is embedded in the polar phase of urea-formaldehyde resin to reduce intermolecular friction; microcrystalline wax is enriched on the particle surface to reduce interfacial shear stress with the metal screw / die orifice; the synergistic effect of these three components increases the melt flow rate by 29% and reduces extrusion power by 17%.
[0021] Optionally, the resulting anti-reversion agent predispersed masterbatch can be used in tire or rubber product processing.
[0022] Through the above technical solution, the masterbatch prepared in the aforementioned embodiments is directly fed into an internal mixer and mixed with a natural rubber / butadiene rubber / carbon black N234 system. The anti-reversion agent is uniformly distributed in the rubber network as a nanoscale dispersed phase (DLS measured Z-avg = 86nm). Its amide groups compete with polysulfide bonds for active sulfur in the early stages of vulcanization, inhibiting C–S bond breakage and rearrangement, thereby delaying the degradation of the crosslinked network. This mechanism is demonstrated in dynamic fatigue testing: the tire tread rubber using the masterbatch of this invention can withstand 50℃ × 10... 7 The length of the crack after flexure was only 58% of that in the control group (direct powder injection). Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 A process flow diagram of a method for resource utilization of aldehyde-containing wastewater for preparing anti-sulfurization reversion agent pre-dispersion masterbatch is provided in an embodiment of this application; Figure 2 The chemical structural formula of citrate amide provided in one embodiment of this application is shown below. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0026] Furthermore, the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this article, unless otherwise specified, generally indicates that the preceding and following related objects have an "or" relationship.
[0027] The embodiments of this application will now be described in further detail with reference to the accompanying drawings.
[0028] Example 1 This embodiment aims to verify the feasibility and overall performance of the present invention under the optimal combination of process parameters. See [link to documentation]. Figure 1 The process flow is shown, and the specific implementation is as follows: 100 kg of formaldehyde-containing wastewater (formaldehyde content 10.0%) was taken. Based on a formaldehyde to urea molar ratio of 2.0:1, 22.4 kg of urea was weighed and added to a 500 L enamel-lined reactor. The wastewater was drawn into the reactor under vacuum (-0.08 MPa), and 112 g of p-toluenesulfonic acid (0.5% of the urea mass) was added. Anchor stirring (60 rpm) was started, and the temperature was raised to 82℃ and maintained for 1.0 h. Subsequently, the temperature was raised to 108℃ and the reaction continued for 4.0 h. The water evaporated during the reaction was collected in a condenser, with a cumulative condensate volume of 23.6 kg. After the reaction, a sample was taken, and the residual formaldehyde content was determined by gas chromatography (GC-FID, external standard method) to be 0.06%, meeting the termination criterion. The reactants were discharged from the bottom of the reactor and filtered through a plate and frame filter press (filtration pressure 0.3 MPa) to obtain a white filter cake. The filter cake was placed in a forced-air drying oven and dried at 90°C for 5 h to constant weight, yielding 31.2 kg of urea-formaldehyde resin with a yield of 87.3%.
[0029] 30.0 kg of dried urea-formaldehyde resin, 35.0 kg of citrate-type anti-sulfurization reversion agent pure powder, 20.0 kg of zinc stearate, and 15.0 kg of microcrystalline wax were added to an SHR-500A high-speed mixer at 800 rpm for 10 min of premixing. The mixture was then melt-extruded using a TE-35 twin-screw extruder (L / D = 40). The temperatures of each zone were set as follows: Zone I 115℃, Zone II 120℃, Zone III 125℃, Zone IV 128℃, and die 125℃. The screw speed was 300 rpm, and the feed rate was 25 kg / h. After water bath cooling and rotary pelletizing, the extruded strips were fed into a JY-1200 vibrating grading screen (screen apertures of 2.0 mm and 3.0 mm) to collect the 2.0–3.0 mm particle size range, yielding 98.6 kg of light yellow granular masterbatch.
[0030] The masterbatch D was measured using a laser particle size analyzer (Malvern Mastersizer 3000). 50 = 2.43 mm, particle size distribution span Span = (D 90 D 10 ) / D 50 = 0.38; X-ray diffraction (XRD) analysis showed that the intensity of the characteristic peak (2θ = 19.2°) of the citrate-type anti-sulfurization reversion agent in the masterbatch was 62% lower than that of the pure powder, indicating that it was highly dispersed; DSC test showed that the melting range of the masterbatch was 122-129℃, with no sharp crystallization peaks, confirming that it was a homogeneous blend system.
[0031] The results show that this embodiment successfully prepared a pre-dispersed masterbatch of anti-sulfurization reversion agent with uniform particle size and good component dispersion. Its physicochemical parameters completely fell within the range defined in the embodiment, verifying the repeatability and technical feasibility of the core process of this invention.
[0032] Example 2 The purpose of this embodiment is to verify the process adaptability and product performance under the lower limit of formaldehyde content (8%) in this application.
[0033] Under the same preparation conditions as in Example 1, only the aldehyde-containing wastewater was replaced with a batch (125 kg) containing 8.0% formaldehyde. Based on a formaldehyde to urea molar ratio of 1.5:1, 22.4 kg of urea was weighed. The remaining steps were the same as in Example 1. After the reaction, the residual formaldehyde content was found to be 0.05%. The filter cake was dried at 85°C for 6 h to obtain 29.8 kg of urea-formaldehyde resin. Premixing and extrusion parameters were the same as in Example 1, yielding 97.2 kg of granular masterbatch.
[0034] Laser particle size analysis shows D 50 = 2.39 mm, Span = 0.41; the intensity of the characteristic peak of the citrate-type anti-sulfurization reversion agent decreased by 58% in XRD; the DSC melting range was 121-128℃.
[0035] The results show that the product can still achieve the technical effects of the present invention, thus proving that the technical solution of the present invention has good feasibility and stability within the formaldehyde content range of 8% to 15%.
[0036] Example 3 The purpose of this embodiment is to verify the process adaptability and product performance under the condition of the upper limit of formaldehyde content (15%) in this application.
[0037] Under the same preparation conditions as in Example 1, only the aldehyde-containing wastewater was replaced with a batch containing 15.0% formaldehyde (83.3 kg). Based on a formaldehyde to urea molar ratio of 2.5:1, 22.4 kg of urea was weighed, and the catalyst was replaced with 224 g of ammonium sulfate (1.0% of the urea mass). The remaining steps were the same as in Example 1. After the reaction, the residual formaldehyde content was found to be 0.08%. The filter cake was dried at 95°C for 4 h to obtain 32.1 kg of urea-formaldehyde resin. The premixing and extrusion parameters were the same as in Example 1, yielding 99.5 kg of granular masterbatch.
[0038] Laser particle size analysis shows D 50 = 2.46 mm, Span = 0.39; the characteristic peak intensity of the citrate-type anti-sulfurization reversion agent decreased by 65% in XRD; the DSC melting range was 123–130℃.
[0039] The results show that the product can still achieve the technical effects of the present invention, thus proving that the technical solution of the present invention has good feasibility and stability within the formaldehyde content range of 8% to 15%.
[0040] Example 4 The purpose of this embodiment is to verify the sufficiency of the reaction and the safety of the product under the lower limit of catalyst dosage (0.1%) in this application.
[0041] Under the same preparation conditions as in Example 1, only the amount of p-toluenesulfonic acid was adjusted from 112 g to 22.4 g (0.1% of the urea mass). The remaining steps were the same as in Example 1. After the reaction, the residual formaldehyde content was found to be 0.09%, and the filter cake was dried at 90°C for 5 h to obtain 30.9 kg of urea-formaldehyde resin. The premixing and extrusion parameters were the same as in Example 1, yielding 98.1 kg of granular masterbatch.
[0042] GC-FID tracking analysis showed that under these conditions, the hydroxymethylation conversion rate was 86.2% after the first stage reaction at 82℃ for 1 h, and the total formaldehyde conversion rate reached 99.91% after the second stage reaction at 108℃ for 4 h, which met the standards of this application; XRD and DSC data were the same as in Example 1.
[0043] The results show that even under the lower limit of catalyst dosage, the present invention can still achieve deep conversion of formaldehyde and stable preparation of masterbatch, verifying the robustness of the process.
[0044] Example 5 The purpose of this embodiment is to verify the resin processing suitability under the lower limit of the drying temperature (85°C) in this application.
[0045] With all other preparation conditions the same as in Example 1, only the drying temperature was adjusted from 90°C to 85°C and the drying time was extended to 7 h until constant weight was obtained, yielding 30.5 kg of urea-formaldehyde resin. The remaining steps were the same as in Example 1, yielding 97.8 kg of granular masterbatch.
[0046] The measured MFI (190℃ / 2.16kg) of the urea-formaldehyde resin was 9.8 g / 10min, slightly higher than that of Example 1 (9.2 g / 10min), but still within the extrusion window of 120-130℃; Masterbatch D 50 = 2.41 mm, Span = 0.40, XRD and DSC data are consistent.
[0047] The results show that the resin dried at 85℃ still has good thermoplasticity and supports subsequent melt blending, verifying the rationality of the parameter range of this application.
[0048] Example 6 The purpose of this embodiment is to verify the quality of masterbatch molding under the lower limit of the melt extrusion temperature (120°C) in this application.
[0049] With all other preparation conditions the same as in Example 1, only the temperatures of Zones III and IV of the twin-screw extruder were uniformly adjusted from 125°C and 128°C to 120°C, and the die temperature was simultaneously adjusted to 120°C. All other parameters remained unchanged, yielding 96.3 kg of granular masterbatch.
[0050] Masterbatch D was measured 50 = 2.37 mm, Span = 0.43; the melt pressure fluctuation range increased by 12% compared with Example 1, but was still within the allowable range of the equipment; SEM observation showed that the surface smoothness of the particles decreased slightly, but the internal dispersion uniformity (EDS surface scan RSD = 8.2%) was comparable to that of Example 1 (8.4%).
[0051] The results show that effective plasticization and dispersion can still be achieved at 120℃, verifying the feasibility of the lower limit of the temperature range of this application.
[0052] Example 7 The purpose of this embodiment is to verify the universality of the preferred ratio in this application under non-optimal parameter combinations.
[0053] With other preparation conditions the same as in Example 2, only the components were adjusted by weight to: 30 parts urea-formaldehyde resin, 35 parts citrate-type anti-sulfurization reversion agent pure powder, 20 parts zinc stearate, and 15 parts microcrystalline wax (i.e., the preferred proportions of this application), to obtain 97.5 kg of granular masterbatch.
[0054] Masterbatch D was measured 50= 2.40 mm, Span = 0.39; vulcanizer tests show that this masterbatch in NR / SBR rubber compound t 90 = 12.8 min, Δt 90 = 2.2 min, compared with Example 1 (Δt) 90 = 2.1 min) is basically the same.
[0055] The results show that the optimal formulation of this application can maintain excellent performance under different wastewater concentrations, providing support for its use as a standardized process parameter.
[0056] Example 8 To systematically evaluate the technical effect of the anti-sulfurization reversion agent predispersant masterbatch prepared by this invention, the following comparative experiments were conducted: 1. Comparative Example 1 (Blank Control): NR / SBR base compound without any anti-reversion agent; 2. Comparative Example 2 (outside the parameter range): Urea-formaldehyde resin was prepared using wastewater with a formaldehyde content of 16% (outside the scope of this application), and the rest was the same as in Example 1; 3. Comparative Example 3 (commercially available product): a certain imported citrate-type anti-sulfurization reversion agent powder (model X-100); 4. Comparative Example 4 (Missing Functional Component): Zinc stearate was omitted, and the rest was the same as in Example 1.
[0057] All samples were prepared as standard test pieces under the same formulation (NR 60 phr, SBR 40 phr, carbon black N234 50 phr, zinc oxide 5 phr, stearic acid 2 phr, accelerator CZ 1.5 phr, sulfur 2.0 phr) at 160℃ for 15 min, and the following tests were performed: (1) Dispersion uniformity: SEM-EDS was used to scan the cross-section of the vulcanized rubber and the standard deviation (RSD) of the distribution of anti-vulcanization reversion agent element (N element) was statistically analyzed. (2) Vulcanization characteristics: t was measured using an MDR 2000E vulcanizer (160℃). 90 With Δt 90 (After 100℃×72h thermo-oxidative aging t) 90 Change value); (3) Dynamic fatigue performance: According to GB / T 13935–2013, a flexure test was conducted at 50℃ (frequency 30 cpm), and the results were recorded for 10 minutes. 7 Length of the subsequent crack; (4) Environmental compliance: Formaldehyde emission (mg / m²·h) was tested in accordance with EN 71-10 / 11 standards.
[0058] The test results are shown in Table 1: Table 1 Results of the effect test
[0059] As shown in Table 1, the embodiments of the present invention are significantly superior to all comparative examples in terms of dispersion uniformity (RSD reduced by approximately 55%), Δt 90 The lowest time was 2.0 min, a 47.4% reduction compared to Comparative Example 1, indicating a significant effect in resisting sulfur reversion; 10 7 The secondary flexural crack length was only 33.3% of that in Comparative Example 1, confirming its substantial improvement in tire durability; the formaldehyde emission was <0.01 mg / m²·h, meeting the most stringent standards for materials in contact with infant toys. Notably, Comparative Example 2's formaldehyde emission reached 0.13 mg / m²·h due to excessive formaldehyde, validating the necessity of the concentration range set in this application; the RSD of Comparative Example 4 increased to 16.5% after the absence of zinc stearate, demonstrating its crucial role in regulating melt rheology and dispersion. In summary, this invention not only solves the problems of "high processing costs, significant pollution, and unutilized resources" in the prior art, but also achieves unexpected technical effects such as "unexpectedly excellent dispersibility, significantly improved thermo-oxidative stability, and breakthrough compliance with environmental protection standards."
[0060] Example 9 In this application example, the test samples included the anti-reversion agent pre-dispersion masterbatches prepared according to each embodiment of Examples 1-7, used in tire tread compound formulations (NR 60 phr, SBR 40 phr, carbon black N234 50 phr, etc.). Standard test pieces were prepared under vulcanization conditions of 160℃×15 min, and tensile strength and elongation at break were tested according to GB / T 528–2009, and resilience was tested according to GB / T 1681–2009. The results are shown in Table 2: Table 2 Test Results of Tire Tread Compound
[0061] According to Table 2, the masterbatches prepared in all examples exhibited superior mechanical properties and resilience compared to the blank control in tire tread rubber, with an average increase of 12.1% in tensile strength and 6.5% in resilience. Furthermore, the data showed minimal fluctuations among the examples (tensile strength RSD = 1.0%), demonstrating that the present invention can stably achieve the technical effect of "for tire or rubber product processing" within the defined parameter range. Experimental results show that the anti-reversion agent pre-dispersion masterbatch prepared in this invention exhibits good anti-reversion and dynamic durability effects in tire tread rubber, and therefore can be used to prepare rubber products for preventing and / or treating early tire cracking and performance degradation caused by reversion.
[0062] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A method for the resource utilization of pre-dispersed masterbatch for preparing anti-sulfurization reversion agent from aldehyde-containing wastewater, characterized in that, include: S1. Formaldehyde-containing wastewater generated during the production of tackifying resin and urea are fed together at a molar ratio of formaldehyde to urea of 1.5 to 2.5:
1. A condensation reaction is carried out in the presence of a catalyst. The condensation reaction is carried out in two stages: the first stage is carried out at 80 to 85°C for 0.5 to 1 hour, and the second stage is carried out at 105 to 110°C for 3 to 5 hours. S2. The reaction product obtained in step S1 is filtered and dried to obtain urea-formaldehyde resin. S3. The urea-formaldehyde resin obtained in step S2, the pure powder of citramide-type anti-sulfurization reversion agent, zinc stearate and microcrystalline wax are premixed and then melt-extruded, granulated and graded to obtain the anti-sulfurization reversion agent pre-dispersion masterbatch. The components in step S3, by mass, include: 25-35 parts of urea-formaldehyde resin, 30-40 parts of pure powder of citrate-type anti-sulfurization reversion agent, 15-25 parts of zinc stearate, and 10-20 parts of microcrystalline wax.
2. The method according to claim 1, characterized in that, The formaldehyde content in the aldehyde-containing wastewater is 8% to 15%.
3. The method according to claim 2, characterized in that, The catalyst mentioned in step S1 is p-toluenesulfonic acid or ammonium sulfate.
4. The method according to claim 3, characterized in that, The amount of catalyst added is 0.1% to 1.0% of the urea mass.
5. The method according to claim 4, characterized in that, After the reaction in step S1 is completed, a sample is taken for testing. The reaction is terminated when the residual formaldehyde content is less than 0.1%.
6. The method according to claim 5, characterized in that, The drying temperature in step S2 is 85–95°C.
7. The method according to claim 6, characterized in that, The melt extrusion temperature in step S3 is 120–130°C.
8. The method according to claim 7, characterized in that, The grading in step S3 is vibration grading.
9. The method according to claim 8, characterized in that, The preferred components in step S3 by mass are: 30 parts urea-formaldehyde resin, 35 parts citrate-type anti-sulfurization reversion agent pure powder, 20 parts zinc stearate, and 15 parts microcrystalline wax.
10. The method according to claim 9, characterized in that, The obtained anti-reversion agent pre-dispersion masterbatch is used in tire or rubber product processing.